2018
DOI: 10.1177/1747954118755443
|View full text |Cite
|
Sign up to set email alerts
|

Sport commitment in young soccer players: A self-determination perspective

Abstract: Objectives: Grounded on the self-determination theory, the aim of this study was to assess the impact of perceived need support/thwarting, psychological needs satisfaction/frustration and motivation on young soccer players' sport commitment. Equipment and methods: We used a sample of 430 male soccer players (M age ¼ 14.21 years, SD ¼ 1.67 years, range ¼ 12-18 years). Results: Structural equation model analysis (2 /df ¼ 2.31; CFI ¼ 0.91, TLI ¼ 0.89, GFI ¼ 0.91, SRMR ¼ 0.03, RMSEA ¼ 0.05) showed that coach suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 31 publications
11
56
1
10
Order By: Relevance
“…It has been argued that developing this energy of self, considered as the experience of feeling alive, vigorous, and energetic, depends to a large degree on the motivational climate created by significant others, in our case the coach ( Ryan and Frederick, 1997 ; Ryan and Deci, 2017 ). In this regard, it is essential to promote coaches’ autonomy-supportive interpersonal styles, not only due to the benefits announced in this study, but also because the literature has associated this interpersonal style with other positive consequences, such as being active ( Fenton et al, 2017 ), the intention to be active and adherence to the sport ( Álvarez et al, 2012 ; Quested et al, 2013 ; Cuevas et al, 2014 ), effort and satisfaction with the coach’s leadership ( Álvarez et al, 2013 ), sport commitment ( Pulido et al, 2018 ), or sportsmanlike attitudes ( Sánchez-Oliva et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been argued that developing this energy of self, considered as the experience of feeling alive, vigorous, and energetic, depends to a large degree on the motivational climate created by significant others, in our case the coach ( Ryan and Frederick, 1997 ; Ryan and Deci, 2017 ). In this regard, it is essential to promote coaches’ autonomy-supportive interpersonal styles, not only due to the benefits announced in this study, but also because the literature has associated this interpersonal style with other positive consequences, such as being active ( Fenton et al, 2017 ), the intention to be active and adherence to the sport ( Álvarez et al, 2012 ; Quested et al, 2013 ; Cuevas et al, 2014 ), effort and satisfaction with the coach’s leadership ( Álvarez et al, 2013 ), sport commitment ( Pulido et al, 2018 ), or sportsmanlike attitudes ( Sánchez-Oliva et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…Following these contributions, Pulido, Sánchez, Sánchez, Amado and García (2018) indicated that the training environment created by the coach can be crucial for the satisfaction or frustration of basic psychological needs and, as a consequence, could play an important role in the sports commitment of young soccer players. Ureña, Chinchilla and Castillo-Rodríguez (2020) showed that young soccer players have fluctuations in motivation depending on the context that surrounds them, so that the coach must design tasks for training, using an appropriate and active methodology, very similar to the experiences soccer players encounter in competition, with problem solving and global tactical approaches, since intrinsic motivation greatly increases.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors (lack of enjoyment, perceptions of competence, social pressures, competing priorities and injuries) affect the sports dropouts of young athletes, highlighting the lack of competence at the time of the decision [ 35 , 38 ], which can cause poor performance [ 39 ]. In this sense, numerous studies show that coaches have a great influence on athletes [ 33 , 40 , 41 ]. In fact, the motivational model of the coach–athlete relationship describes how coaches may influence athletes’ motivation, meaning that they are important determinants of performance and persistence [ 42 ].…”
Section: Introductionmentioning
confidence: 99%